Measuring The Consistency Of Female Voters In The Practice Of Money Politics - Nurul Chamidah; Khaerudin Imawan (Jurnal Ilmu Komunikasi, 2018)
The practice of money politics occurs in the event of Local Leaders Selection (Pilkada). Although emerging debates, the community is in fact still categorized as highly enjoying the practice of corruption in the process of democracy in Indonesia. The practice is forbidden and has legal consequences, however, the “gratification” of rupiah towards the election day which known in the term of “dawn bribery” is still accepted by constituents especially by the women voters. This research was conducted on the election of local leaders of Cirebon Regency in 2013 and 2018 by implementing mix method analysis. Quantitative data were acquired through survey questionnaire with multistage random sampling system and qualitative data were obtained through interview and observation towards the participants. The results of research have indicated that the community considers the money politics as common thing and it tends to be the awaited moment as the form of “political fortune”. About 75% of voters consider money politics as a common thing. Even though, money politics did not influence the voters in determining their attitude. Female voters are still influenced by collectiveness culture and domination of family head in determining their political choices. The role of stakeholders and political education for women are required to change the political attitude of voters in having a healthy politics.